Implementation of STEM Integrated Project Based Learning (PjBL) to Improve Problem Solving Skills - Maharani Ayu Nurdiana Putri; Dwikoranto Dwikoranto (Berkala Ilmiah Pendidikan Fisika, 2022)
The 4Cs are skills that emphasize learning across the 21st century (Critical thinking, Communication, Collaboration, Creativity). Problem-solving, one of the 21st century's skills, developed by implementing PjBL-STEM learning models. PjBL-STEM learning focuses on developing students' ability to be more engaged, innovative, and open to the idea of concepts learnt through project-based activities that incorporate STEM aspects in real life. The study's goal is to examine how PjBL-STEM learning improves problem-solving skills. The research method used was quantitative research through a one-group pre-experimental design with pretest and posttest. A total of 35 students from class XI IPA 2, SMA X Muhammadiyah Surabaya, participated in the study.  This study uses purposive sampling to consider students' abilities and conditions of delivery of subject matter. The study's results (N-gain) were 0.59, classified as "medium".  According to the findings of this study, Learning the PjBL-STEM model has been sufficient for enhancing problem-solving abilities in dynamic fluid materials. The characteristics of the PjBL-STEM learning model that focuses on the 'student-centred model' significantly influence problem-solving skills. The advantages of this model should be accompanied by improvement of educational facilities and teaching skills in the learning process in order to create a balanced learning environment